2008
DOI: 10.1111/j.1076-7460.2007.07242.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combination Evidence‐Based Medical Therapy on Mortality Following Myocardial Infarction in Elderly Patients

Abstract: Antiplatelet drugs, beta-blockers, statins, and angiotensinogen-converting enzyme inhibitors reduce mortality following myocardial infarction (MI). The data on the impact of combination evidence-based medications on mortality following acute MI in elderly patients are limited. In this study, 5529 patients with MI admitted between January 2000 and December 2003 were assessed. Based on discharge use of evidence-based medications, the patients were divided into those using 0, 1, 2, 3, or 4 medications. The impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
1
17
1
1
Order By: Relevance
“…However, these studies are likely to be confounded by healthy user bias and are too small to answer the question of comparative effectiveness of specific drug combinations, with most enrolling fewer than 6000 patients. [397][398][399][400][401] The MINAP registry is substantially larger and has provided, for the first time, the opportunity to evaluate the comparative effectiveness of aspirin, clopidogrel, beta-blockers, ACEIs and statins individually and in all combinations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are likely to be confounded by healthy user bias and are too small to answer the question of comparative effectiveness of specific drug combinations, with most enrolling fewer than 6000 patients. [397][398][399][400][401] The MINAP registry is substantially larger and has provided, for the first time, the opportunity to evaluate the comparative effectiveness of aspirin, clopidogrel, beta-blockers, ACEIs and statins individually and in all combinations.…”
Section: Introductionmentioning
confidence: 99%
“…In conseguenza le linee guida raccomandano l'utilizzo routinario di questi farmaci [1][2][3]. Infatti, Goldberg et al [4], usando i dati dello studio GRACE (Global Registy of Acute Coronary Events), su 26.413 pazienti senza controindicazioni alla loro assunzione, hanno rilevato, dopo l'implementazione delle linee guida, un deciso aumento dal 2000 al 2005 nell'assunzione di statine (dal 45% al 85%), ACE-I (dal 63% al 77%), betabloccanti (al 83% al 91%) e ASA (circa 95%).…”
Section: Introduzioneunclassified
“…Over the past several decades, advances in the medical treatment of coronary heart disease have resulted in a significant decline in hospital and short‐term mortality . Numerous clinical trials have demonstrated the efficacy of 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase inhibitors (statins), beta‐blockers (BBs), angiotensin‐converting enzyme inhibitors (ACEIs), angiotensin‐II receptor blockers (ARBs), and antiplatelet agents such as clopidogrel for secondary prevention in individuals who have had an AMI . Use of these evidence‐based medications is now a cornerstone of long‐term medical therapy in this population…”
mentioning
confidence: 99%